The Effectiveness of Istighfar Dhikr Therapy in Reducing Anxiety in Female Breast Cancer Patients - NH, Rika Sylvia; Nashori, Fuad (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
Women with breast cancer face physical and psychological impacts, including anxiety characterized by fear of not being able to do activities, lack of self-confidence, fear of being in crowds, and fear of death. To reduce this anxiety, the study used istigfar dhikr therapy as an intervention. This study aims to evaluate the effectiveness of istigfar dhikr therapy in reducing anxiety in women with breast cancer. The study was conducted with a quantitative quasi-experimental approach, using a control groups pretest-posttest with follow-up design. A total of 12 participants were divided into control groups (n=6) and experiments (n=6), selected by purposive sampling. Measurements were taken using the Hospital Anxiety and Depression Scale (HADS), while therapy referred to the Ruidahasi et al. module. Analysis using Anova Mixed Design showed significant results (Sig. 0.000, p<0.05), with an effective contribution of 91.4%, proving that this therapy is effective in reducing anxiety.